CD4+:CD8+ T Cell Ratio Normalization and the Development of AIDS Events in People with HIV Starting Antiretroviral Therapy - Okhai, Hajra (AIDS Res Hum Retroviruses, 2020)
We identify factors associated with the normalization of the CD4+:CD8+ T cell ratio among UK Collaborative HIV Cohort study participants, and describe the association of the CD4+ and CD8+ T cell counts and the CD4+:CD8+ T cell ratio, with the risk of new AIDS events among individuals who achieve a suppressed viral load. Participants initiating combination antiretroviral therapy (cART) after 2006 with a CD4+:CD8+ T cell ratio <1, and viral suppression within 6 months were included. Cox proportional hazard models were used to examine associations with ratio normalization (ratio ≥1). Poisson regression models were used to investigate factors associated with the development of AIDS after viral load suppression. A total of 13,178 participants [median age: 37 (interquartile range: 31–44)] were followed for 75,336 person-years. Of the 4,042 (32.9%) who experienced ratio normalization, individuals with a high CD4+ T cell count [>500 vs. ≤200 cells/mm(3), adjusted hazard ratio (95% confidence interval): 7.93 (6.97–9.01)], low CD8+ T cell count [>1,150 vs. ≤500 cells/mm(3): 0.18 (0.16–0.21)], and low CD4+:CD8+ T cell ratio [>0.8 vs. <0.2: 12.36 (10.41–14.68)] at cART initiation were more likely to experience ratio normalization. Four hundred and nineteen people developed a new AIDS event. Most recent CD4+ T cell count [>500 vs. ≤200 cells/mm(3): adjusted rate ratio 0.24 (0.16–0.34)] and CD4+:CD8+ T cell ratio [>0.8 vs. <0.2: 0.33 (0.21–0.52)] were independently associated with a new AIDS event. One third of study participants experienced ratio normalization after starting cART. CD4+ T cell count and CD4+:CD8+ T cell ratio are both individually associated with ratio normalization and the development of new AIDS events after cART.